Oncovascular Resection of a Ganglioneuroma Involving the Coeliac Trunk and Hepatic Artery—A Case Report. (July 2021) - Lawrie, Kateřina; Whitley, Adam; Rokošný, Slavomír; Bafrnec, Jan; Gürlich, Robert; Baláž, Peter
A large tumorous mass completely surrounding and compressing the coeliac trunk was identified on computed tomography in a young woman with a six-month history of progressive abdominal pain. The tumor was excised along with the coeliac trunk and the proximal parts of its branches. The hepatic artery was reconstructed with an aorto-hepatic autogenous bypass. Postoperatively the patient had neurogenic diarrhea, which subsided on medical treatment. Seven months after surgery the patient is in a good state of health and living a normal life.